SapF-mediated heme-iron utilization enhances persistence and coordinates biofilm architecture of Haemophilus - Vogel, Andrew R.; Szelestey, Blake R.; Raffel, Forrest K.; Sharpe, Samantha W.; Gearinger, Rachel L.; Justice, Sheryl S.; Mason, Kevin M. (Frontiers in Cellular and Infection Microbiology, 2012)
Nontypeable Haemophilus influenzae (NTHI) is a common commensal bacterium that resides in the human upper respiratory tract of healthy individuals. NTHI is also a known causative agent of multiple diseases including sinusitis, otitis media as well as exacerbates disease severity of patients with cystic fibrosis and chronic obstructive pulmonary disease. We have previously shown that the Sap ABC transporter mediates resistance to host antimicrobial peptides (AMPs) and import of the iron-containing compound heme. Here, we analyzed the contribution of the Sap structural ATPase protein, SapF, in these essential functions. SapF was dispensable for NTHI survival when exposed to AMPs in vitro. SapF was responsible for heme utilization and recovery of depleted internal heme iron stores. Further, a loss of SapF resulted in morphological plasticity and enhanced community development and biofilm architecture, suggesting the potential role of heme iron availability in coordinating the complexity of NTHI biofilm architecture. SapF was required for colonization of the nasopharynx and acute infection of the middle ear, as SapF deficiency correlated with a statistically significant decrease in NTHI persistence in vivo. These data suggest that SapF is required for proper heme utilization which directly impacts NTHI survival. Thus, these studies further support a role for the Sap complex in the transport of multiple substrates and further defines substrate specificity for the two ATPase subunits. Given the multiple essential functions provided by the Sap ABC transporter, this complex could prove to be an effective therapeutic target for the treatment of NTHI diseases.